Balancing Privacy: Sharenting, Intimate Surveillance, and the Right to Be Forgotten - Leaver, Tama (Routledge, 2021)
In the era of sharenting, apps, platforms, and infant wearables, balancing children’s right to privacy is a task that often falls to new parents who may find themselves ill equipped to navigate the many challenges that come with protecting children’s online presence and data. This chapter examines how parent and child influencers act as privacy role models, and how sharenting provokes new parenting challenges; it weighs these against a child’s right to privacy and, perhaps, their right to be forgotten.